IMPLEMENTASI KURIKULUM PASCAPANDEMI DALAM PEMBELAJARAN SEJARAH DI ERA DIGITAL DAN GLOBAL: SEBUAH KAJIAN LITERATUR - Siti Herdiyanti Wijaya (Jurnal Pendidikan Sejarah Indonesia, 2026)
The COVID-19 pandemic has had a significant impact on various sectors, including education. The sudden shift to online learning forced the education system to adapt quickly. This research aims to explore how the post-pandemic curriculum can be adapted to new conditions in the digital and global era. The research method used is a literature review, by collecting, analyzing and synthesizing various literature related to educational transformation during the pandemic and post-pandemic. The research results show that the post-pandemic curriculum must emphasize digital literacy, critical thinking skills, collaboration, and flexibility in learning. In addition, deeper technology integration is needed to support hybrid learning and personalization of education. This study also underscores the importance of an inclusive approach to ensure equitable access to education amidst the digital divide. By adopting an adaptive curriculum, the education system is expected to be able to meet the needs of students in the era of globalization and digital transformation. Keywords: Curriculum, digital education, educational transformation.